OBSERVA nONS ON THE FOOD AND FEEDING HABITS OF SARDINELLA GIBBOSA FROM VIZHINJAM - Lazarus, S (Indian Journal of Fisheries, 2011)
Except for a brief note by Chidambaram (1942), the existing information on :the food and fe,eding habits of the Indian sprat, Sardinella gibbosa, relates ,exclusively to the e,ast coa’st of Indila: (Devanesan 1932, 1942; Chacko 1946, 1949 and 1956; Devanesan and Chidamball"am 1948; Ganapati and Rao 1957; Kuthalingam 1961 and Sekhalran 1971). ’J1he present study carried out at Vizhinjam 0!Il the west ooast of Ind1a attempts to find out the aceas of similarity and dissimilarity, if any, as compar’edto the ,earlier studies on the east coast.